Child Education in the Family as an Early Childhood Education Strategy During the Covid-19 Pandemic - Oktaria, Renti; Putra, Purwanto (Jurnal Ilmiah Pesona PAUD, 2020)
At present, education in the family is a surefire strategy to continue to provide education rights to early childhood. The role of parents is now tested by the covid-19 pandemic that is sweeping the country. Many things must also be considered in providing education in the family, namely health factors, children’s eating and drinking needs, and also related to psychological, early childhood comfort when studying or playing at home. Through a descriptive study approach with ten parents with a master’s education background and academics as respondents through digital questionnaires and interviews with the Google form application. The results of the questionnaire and interviews were analyzed by means of descriptive analysis. It was found that: (1) Only three out of ten parents can adjust to the role of educators for their own children and able to create comfort when providing learning to children at home; (2) Three out of ten parents are able to establish good communication with teachers during educational activities from home; (3) ten parents expressed their concern with the existing conditions and agreed that the role of teachers was not easy o live. Keywords  : education in the family; parenting